(untitled) (European Journal of Pure and Applied Mathematics, 2025)
In this article, we introduce a self-adaptive method for approximating solutions of split common fixed point problem of Bregman demigeneralized mappings and systems of monotone variational inclusion problem with multiple output sets in reflexive Banach spaces. By employing our iterative method, we prove a strong convergence theorem for approximating solutions of the aforementioned problems. In sum, we state some consequences of our main result. The result discuss in this paper extends and complements many related results in literature.